Penulis PENGARUH RASIO LIKUIDITAS TERHADAP KESEHATAN KEUANGAN DANA TABARRU ASURANSI JIWA SYARIAH (STUDI KASUS PERUSAHAAN ASURANSI JIWA BERDASARKAN AASI PERIODE 2017-2021) - regi utami (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The purpose of this study is to determine the effect of liquidity ratio on the financial health of sharia life insurance tabarru funds in insurance companies registered with the Indonesian Sharia Insurance Association. The method used in this study is quantitative method and also uses secondary data obtained from financial statements starting from 2017 to the end of 2021 in full. As for the population, it was carried out from data on insurance companies that had been registered with the AASI institution as many as 20 companies while the sample in the study was 8 companies. The analysis technique used is simple linear regression analysis. The result is that the ratio of liquidity and financial health has a calculated t value of 7.309 with a Sig of 0.000 with a calculated t value of 7.309 > 2.204 and a level of 0.000 <0.05. So it is concluded that the variable liquidity ratio has an influence on the financial health of tabarru funds.